Keberadaan Plastik di Lingkungan, Bahaya terhadap Kesehatan Manusia, dan Upaya Mitigasi: Studi Literatur - Yura Witsqa Firmansyah; Mirza Fathan Fuadi; Muhammad Fadli Ramadhansyah; Farida Sugiester S; Wahyu Widyantoro; Maurend Yayank Lewinsca; Sutra Diyana; Nanda Ika Vera Marliana; Intan Sekar Arumdani; Aziz Yulianto Pratama; Desti Azhari; Ramadani Sukaningtyas; Afdal Hardiyanto (Fakultas Teknik, 2021)
Since 2001, synthetic polymers have been one of the most important materials since 2001 because they are used by humans and become a necessity in various sectors such as thermoplastics in countless quantities. Plastics have properties that are difficult to decompose and can change size into plastic macromolecules with the help of photodegradation, oxidation, hydrolytic degradation, and mechanical breakdown . Plastic pollution is a serious problem because the demand for plastic by society is increasing every year and the result of a lot of plastic waste can cause serious health problems and problems in the surrounding environment. Therefore, the use of plastic has a big impact on human health and the environment because it’s hard to decompose. The aim of this study is to provide information on the effects of microplastics on the environment through a review study. This study uses a descriptive method with a literature review approach. The criteria for articles used sources from Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, and Emerald Insight. The conclusion in this study found a relationship between the presence of microplastics with human health problems, and the environment so that it is necessary to mitigate against plastic waste pollution such as 3R and substitution of materials.